More Experience, Less Loneliness? Exploring the Effect of Experiential Purchases on the Alleviation of Loneliness - Yang, Bingcheng; Yu, Hongyan; Yu, Yu (Frontiers in Psychology, 2021)
Over the past few decades, researchers have explored the effects of experiential purchases and material purchases on happiness, and provided a range of evidence to support that consumers yield greater happiness from experiential purchases compared to material purchases. However, limited research is known about the relationship between these two types of purchases within the broader context of negative emotion. Specifically, the current research focused on the effect of experiential purchases on loneliness alleviation to replenish this research stream. Three experiments were conducted to explore the effect of experiential purchases (vs. material purchases) on alleviating loneliness. The results showed that experiential purchases have a stronger effect on loneliness alleviation than material purchases, which is mediated by relationship enhancement. In addition, purchases of social nature moderate the effect of experiential purchases on loneliness. Social experiential purchases lead to a higher degree of relief on loneliness. On the contrary, for the solitary experiential purchases, the effect of experiential purchases on loneliness is less tight. The current research supplements the research on negative emotions of experiential purchases and expands the research area of experiential purchases, which also provides new insights into coping strategies of loneliness.